2022
DOI: 10.1080/10826084.2022.2069267
|View full text |Cite
|
Sign up to set email alerts
|

“The Perfect Formula:” Evaluating Health Claims, Products and Pricing on Cannabis Dispensary Websites in Two Recently Legalized States

Abstract: Words: 250Introduction: Many cannabis dispensaries market and sell their products online through websites designed to attract and maintain customers; often, these websites incorporate a variety of product claims and other marketing tactics. This study evaluated website content, product pricing and discounts on dispensary websites in California and Nevada, states that legalized recreational cannabis in 2016. Methods:We content coded product availability, marketing claims and discounts on cannabis dispensary web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…While we did not find explicit claims that cannabis could treat COVID-19, some announcements suggested ways to use cannabis to avoid infection, or suggested cannabis products to use if experiencing anxiety; these implicit connections between cannabis and health are consistent with prior studies finding cannabis dispensary health benefit claims 16 . This analysis was limited only to the COVID-19 announcements; a subsequent analysis of the full website content found that anxiety was the most common mental health claim, present on 80% of websites in this sample 17 . This limited analysis of the COVID-19 announcements from a single time point early in the pandemic likely underestimates the potential influence dispensary marketing could have on cannabis consumption.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…While we did not find explicit claims that cannabis could treat COVID-19, some announcements suggested ways to use cannabis to avoid infection, or suggested cannabis products to use if experiencing anxiety; these implicit connections between cannabis and health are consistent with prior studies finding cannabis dispensary health benefit claims 16 . This analysis was limited only to the COVID-19 announcements; a subsequent analysis of the full website content found that anxiety was the most common mental health claim, present on 80% of websites in this sample 17 . This limited analysis of the COVID-19 announcements from a single time point early in the pandemic likely underestimates the potential influence dispensary marketing could have on cannabis consumption.…”
Section: Discussionsupporting
confidence: 79%
“…16 This analysis was limited only to the COVID-19 announcements; a subsequent analysis of the full website content found that anxiety was the most common mental health claim, present on 80% of websites in this sample. 17 This limited analysis of the COVID-19 announcements from a single time point early in the pandemic likely underestimates the potential influence dispensary marketing could have on cannabis consumption. While COVID-19 announcements had largely disappeared from dispensary websites by October 2021, an informal review of the dispensary websites included in this analysis in October 2021 found that one featured a blog post on the topic, "Can marijuana cure coronavirus?"…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited evidence on the medicinal benefits of cannabis for health-related outcomes, past research has found cannabis retailers use a wide array of health claims to market cannabis on websites (Bierut et al, 2017;Boatwright & Sperry, 2020;Hoeper et al, 2022). In this study, nearly 67% of all retailers displayed physical health claims, and 59% displayed mental health claims.…”
Section: Discussionmentioning
confidence: 66%
“…Health Claims, Positive States, and Clean Labels Health claims were coded into two categories: (1) Physical health claims were defined as any statement or imagery that describes or insinuates a reduced risk of a physical disease or alleviation of a physical health-related condition (e.g., physical pain, cancer), including sleep-related disturbances (e.g., insomnia) (Hoeper et al, 2022). ( 2) Mental health claims describe or imply a relationship between cannabis and alleviation of a psychological health-related condition or mental illness (e.g., anxiety) (Hoeper et al, 2022).…”
Section: Seletion Of Retailer Websitesmentioning
confidence: 99%
“…The crises regarding economics and finance occurred in 2008, which leads to confusion in purchasing products for consumers and the need was arises for online marketing. Consumers compared the product's prices and shapes by using the internet (Hoeper et al, 2022). Due to the increased diversity in the products, individuals are confused and facing difficulties in selecting the suitable and best products for themselves (Ambilkar, Dohale, Gunasekaran, & Bilolikar, 2022;Chen & Chi, 2021).…”
Section: I T E R a T U R E R E V I E Wmentioning
confidence: 99%